Pengaruh Variasi Konsentrasi NaOH sebagai Nutrisi pada Performansi Biogas Tipe Portabel - Syamsuri; Yustia Wulandari Mirzayanti; Wiwik Widyo Widjajanti; Samuel Kristian Bani (Journal of Research and Technology, 2020)
Biogas is a gas fuel produced by anaerobic activity or fermentation of organic materials, including human and animal waste, domestic (household) waste, or anaerobic degradation of organic materials by anaerobic bacteria. In this study, biogas was used as fuel with the addition of NaOH variations to the modified gasoline generator set engine so that it could work to produce electricity. This experiment used variations of 2, 4, 6, 8, and 10% NaOH nutrition with variations in the electric load of 10, 15, 20, 25, 30, 35, 40, 45, and 50 watts. These purposed to determine the performance of electric power, torque, and system efficiency. From the test, it found that the greater load of the lamp, the smaller performance of the electric power produced. The results showed that the greatest electric power was the variation of 2% NaOH nutrition with a lamp load of 10 watts, namely 39.33 watts. In the efficiency testing, the greater electric load system resulted efficiency system tent to be stable. The best system efficiency with 2% NaOH nutrition was compared to other nutritional variations. In testing of torque, the greater electric load torque resulted also greater torque. The greatest torque with 2%, NaOH nutrition compared to other nutritional variations.